Evolution of the Global Overturning Circulation since the Last Glacial Maximum based on marine authigenic neodymium isotopes. (1st August 2020) - Du, Jianghui; Haley, Brian A.; Mix, Alan C.
Abstract: The Global Overturning Circulation is linked to climate change on glacial-interglacial and multi-millennial timescales. The understanding of past climate-circulation links remains hindered by apparent conflicts among proxy measures of circulation. Here we reconstruct circulation changes since the Last Glacial Maximum (LGM) based on a global synthesis of authigenic neodymium isotope records (εNd ). We propose the bottom-up framework of interpreting seawater and authigenic εNd considering not only conservative watermass mixing, but also the preformed properties and the non-conservative behavior of εNd, both subject to sedimentary influences. We extract the major spatial-temporal modes of authigenic εNd using Principal Component Analysis, and make a first-order circulation reconstruction with budget-constrained box model simulations. We show that during the LGM, the source region of North Atlantic overturning shifted southward, which led to more radiogenic preformed εNd of glacial Northern Source Water (NSW). Considering this preformed effect, we infer that glacial deep Atlantic had a similar proportion of NSW as today, although the overall strength of glacial circulation appears reduced from both North Atlantic and Southern Ocean sources, which increased the relative importance of non-conservative behavior of εNd and may have facilitated accumulation of respired carbon in the deep ocean. During the deglaciation, we find that Southern Ocean overturning increased, which offset suppressed North Atlantic overturning and resulted in a net stronger global abyssal circulation. Faster global scale deglacial circulation reduced the relative importance of non-conservative effects, resulting in Atlantic-Pacific convergence of abyssal εNd signatures. Variations of Southern Ocean overturning likely drove a significant fraction of deglacial changes in atmospheric CO2 and oceanic heat budget. Highlights: Sedimentary flux causes non-conservativeness of seawater and authigenic εNd . New framework of using εNd as a circulation tracer includes sedimentary influence. Proportion of northern sourced water similar to today in the glacial deep Atlantic. Southern Ocean circulation strengthened during the deglaciation. Abyssal circulation coupled to carbon cycle and ocean heat budget in the past.